The Effect of Sambung Nyawa Leaf Extract (Gynura procumbens (Lour.) Merr.) on Hemoglobin of Rats Induced by Escherichia coli Bacteria - Asnad Gulo; Pasar M Silitonga (Indonesian Journal of Chemical Science and Technology (IJCST), 2021)
The aim of this research was to study the effect of extract of the sambung nyawa (Gynura procumbens (Lour.)Merr.)) leaf on hemoglobin concentration of rats blood. The research method is experimental used Completely Randomized Design (CRD) that consists of 6 treatments and 3 replications. The treatment of this research was induced rats with E. coli then given 0.5 mL of sambung nyawa leaf extract with doses 0.0 mg/kgBW; 300 mg/kgBW; 600 mg/kgBW and 900 mg/kgBW . The data was analyzed using Analysis of Variance. The results showed that the giving extract of the sambung nyawa leaves gives effect on on hemoglobin concentration of rats blood. Giving sambung nyawa leaf extract at dose 0.00 mg/kgBW; 300 mg/kgBW; 600 mg/kgBW and 900 mg/kgBW to rats gave the average of hemoglobin concentration in a row in each treatment is 10,5 g/dL; 11,7 g/dL; 12,3 g/dL and 13,7 g/dL.